Machinability of Crankshaft Steel: On the Influence of Batch-to-Batch Material Variations - Machado, Tyrone Julius (My University, 2019)
Steel produced in different batches generally have similar macro-mechanical properties due to small variations in the alloying elements – within the standard specifications – and stringent control on post-process treatments such as rolling and subsequent heat treatments. Despite the small variations in macro-mechanical properties, the variations in type, amount, and size distribution of non-metallic inclusions (NMIs) present within the steel can lead to inconsistent behaviour of material batches during machining. Thus, process planners face a big challenge in achieving a high quality of machined components at low costs due to such production disturbances. This study examines the tool wear during the semi-finishing operation of 5 different batches of crankshafts. Initially, the influence of NMIs and microstructural differences on machinability of different steels reported in the literature was reviewed. Later, an in-depth metallographic analysis was performed on one crankshaft from each batch using optical and electron microscopy to determine the composition, distribution, morphology, size, and type of NMIs along with microstructural differences. Cutting tool inserts from each batch were analysed to determine the wear and layer formation on the cutting surfaces of the inserts. MnS inclusions were the most prominent inclusions followed by complex oxy-sulphide inclusions in smaller numbers with varying morphologies, size, and distribution. The inserts exhibited small differences in the flank and nose wear. However, the topography of the worn surfaces on the rake face was different in some cases. This perhaps indicates the beneficial protective and lubricative effects of layers formed on the tool surfaces due to the presence of soft and chemico-physically stable inclusions.
Keywords: Machinability; Flank wear; Nose wear; Scanning electron microscopy; Non-Metallic Inclusions (NMIs); Crankshaft